Technical Efficiency and Downstreaming in Indonesia’s Basic Metal Industry: A Stochastic Frontier Analysis Approach - Endar Kumalasari (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study measures technical efficiency and identifies the determinants of technical inefficiency in Indonesia’s basic metal industry during 2017 to 2019 by using a translog stochastic frontier model. The analysis employs firm-level data from the annual manufacturing large and medium industry survey (IBS) of Bureau Statistics Indonesia, comprising a balanced panel of a 420 firms with 1,260 observations, and is estimated following the Battese Coelli (1995) with one-step-approach. The results reveal that the basic metal industry is on average 90.58% technically efficient, leaving an aggregate output gap of approximately 11.6%. it is noted that downstreaming depth contributed most strongly to reducing technical inefficiency, followed by import intensity, and export orientation, whereas firm size contributed to higher inefficiency, meanwhile foreign ownership and research and development were found to be insignificant. The estimates of input elasticities indicate that material is the dominant input, and the industry operates under slightly increasing returns to scale. Suggesting that capacity expansion through smelter development remains economically efficient. These findings provide firm-level quantitative evidence that the mineral downstreaming policy is associated not only with higher aggregate value added but also with improved production efficiency.